Revisiting the Analysis of 1988 Radiocarbon Dating of the Shroud of Turin - Arachige, Darshi (Advances in Social Sciences Research Journal, 2017)
This paper revisits the analysis of 1988 radiocarbon dating of the Shroud of Turin published in the Nature in 1989. The radiocarbon dating has been controversial as the sample taken from the Shroud is believed to be contaminated. Arguing from a novel statistical point of view, the current analysis, within the confines of the data provided in the Nature article, further confirms their radiocarbon dates for the Shroud of Turin. It also finds the opposing argument that their result is untenable due to the shortcomings of sample selection arising from the localised heterogeneity such as invisible mending in the selected sample, to be highly unlikely.